2019
DOI: 10.1096/fj.201900857
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginase immune complexes induce Fc‐γRIII–dependent hypersensitivity in naive mice

Abstract: Asparaginase (ASNase) is an important drug for the treatment of leukemias. However, hypersensitivity to ASNase can increase the risk of leukemia relapse. Two mechanisms of ASNase hypersensitivity have been identified in mice. The existence of a pathway involving anti‐ASNase IgG and Fc‐γ receptor III (FC‐γRIII) implies that IgG and ASNase immune complexes (ICs) could directly induce hypersensitivity. The aim of this study was to detect ASNase ICs in mice after hypersensitivity reactions and determine their role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…The decreased antibody levels and fewer ASNase ICs suggest that NFATC2 deficiency could protect against hypersensitivity reactions, at least partially, by downmodulating both the IgE/FceR1 and IgG/FcgRIII pathways of anaphylaxis. 22,23 Because NFATC2 regulates cytokine expression, and cytokines can influence antibody and mast cell responses and responses to mast cell-produced mediators, we next investigated the effect of NFATC2 deficiency on Th2 cells and cytokines.…”
Section: Nfatc2 Ko Mice Are Protected Against Asnase Hypersensitivitymentioning
confidence: 99%
“…The decreased antibody levels and fewer ASNase ICs suggest that NFATC2 deficiency could protect against hypersensitivity reactions, at least partially, by downmodulating both the IgE/FceR1 and IgG/FcgRIII pathways of anaphylaxis. 22,23 Because NFATC2 regulates cytokine expression, and cytokines can influence antibody and mast cell responses and responses to mast cell-produced mediators, we next investigated the effect of NFATC2 deficiency on Th2 cells and cytokines.…”
Section: Nfatc2 Ko Mice Are Protected Against Asnase Hypersensitivitymentioning
confidence: 99%
“…More severe hypersensitivity reactions are indicated by a more significant change in core body temperature and lower AUC values. Throughout our analysis, mice were either sacrificed before or after the onset of hypersensitivity to assess differences in the severity of anaphylaxis as described previously ( 11 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that IgE- and IgG-mediated pathways are involved in ASNase hypersensitivity, both of which are associated with the severity of anaphylaxis ( 11 , 12 ). Based on these results, we have developed tools that can discern between IgE- and IgG-mediated ASNase hypersensitivity ( 11 14 ). Others have explored IgE-mediated basophil activation and measurement of anti-ASNase antibody levels of various antibody isotypes ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The basis of hypersensitivity is undoubtedly immune-mediated [ 4 , 11 , 13 , 14 ]. PEGylation diminishes the immunogenicity of L-asp, and the antibodies in children receiving PEGasp appear to be mostly directed towards PEG rather than towards asparaginase itself [ 11 ].…”
Section: Introductionmentioning
confidence: 99%